2015
DOI: 10.1186/s13643-015-0069-4
|View full text |Cite|
|
Sign up to set email alerts
|

What value is the CINAHL database when searching for systematic reviews of qualitative studies?

Abstract: BackgroundThe Cumulative Index to Nursing and Allied Health Literature (CINAHL) is generally thought to be a good source to search when conducting a review of qualitative evidence. Case studies have suggested that using CINAHL could be essential for reviews of qualitative studies covering topics in the nursing field, but it is unclear whether this can be extended more generally to reviews of qualitative studies in other topic areas.MethodsWe carried out a retrospective analysis of a sample of systematic review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 69 publications
2
32
0
Order By: Relevance
“…These databases were selected because of their known coverage of qualitative literature. 153,154 The other databases from review 1 were not searched because of their focus on quantitative literature, but any qualitative studies identified during study selection in review 1 were marked for possible inclusion in this review. No date restrictions were applied to the search.…”
Section: Search Strategymentioning
confidence: 99%
“…These databases were selected because of their known coverage of qualitative literature. 153,154 The other databases from review 1 were not searched because of their focus on quantitative literature, but any qualitative studies identified during study selection in review 1 were marked for possible inclusion in this review. No date restrictions were applied to the search.…”
Section: Search Strategymentioning
confidence: 99%
“…The finding may also reflect the inclusion of books and book chapters, a potentially rich source of qualitative research, on PsycINFO as well as journal articles. CINAHL also held many of the studies, again to be expected as it is known from previous work that CINAHL has good coverage of qualitative literature . MEDLINE and EMBASE contained fewer of the test set references, possibly reflecting the databases' inclination toward journals that focus on more traditional quantitative studies, although still including at least 70% of the studies.…”
Section: Discussionmentioning
confidence: 99%
“…As qualitative research spans across many disciplines and topic areas, it follows that qualitative studies are published in a wide variety of journals or as books or in book chapters many of which are not indexed on the large databases such as MEDLINE with its heavily clinical focus . Previous studies have assessed the coverage of qualitative research on individual databases and have demonstrated that CINAHL is a good source of qualitative studies in healthcare, particularly in the nursing field, and that searching MEDLINE alone is insufficient for reviews of qualitative studies …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These databases were selected because they collectively afford comprehensive coverage across a range of relevant healthcare disciplines and perspectives (medical, nursing, psychological, and social care); these databases have been commonly used in previous systematic reviews of qualitative healthcare research (Wright, Golder, & Lewis-Light, 2015).…”
Section: Searchingmentioning
confidence: 99%